Planejamento espacial marinho como ferramenta de gest\~ao de política pública para a Amazônia azul - Israel de Oliveira Andrade; Andrea Bento Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
Marine spatial planning (MSP) is an internationally known tool for organizing and governing marine spaces and activities, economic or otherwise, carried out in these spaces. Being a public process of mapping and analyzing the maritime area that involves multiple interests, actors and factors, it proves to be a complex task. The MSP is a necessity for the Brazilian State in line with the commitment made by the country to the international community. This text seeks to begin the discussion of MSP within a theoretical framework of organization of the Brazilian maritime space and the economic importance of activities carried out in this space. As a public policy tool, MSP can contribute to the organization of state actions in the development of the coastal and marine region, including encouraging the transition to the blue economy in the country. Its dynamic character could mitigate marine pollution, eutrophication, water acidification, lost of biodiversity and climate changes, among other issues.
Keywords: Q01; Q25; Q28; 330; blue economy; Blue Amazon; marine spatial planning; South Atlantic; environment